Bracket creeps: Bane or boon for the stability of numerical budget rules? - Martin Altemeyer-Bartscher; Götz Zeddies (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
As taxpayers typically pay low attention to a small inflation-induced bracket creep of the income tax, policy-makers tend to postpone its correction into the future. However, the fiscal illusion fades away and political pressure for a tax relief arises since after some years the cumulative increase of the average tax rate exceeds a critical threshold. Using Germany as an example, this paper shows that bracket creeps can provoke revenue cycles in public budgets hindering governments' compliance with the numerical budget rules. An indexation of the tax tariff could prevent such fluctuations and thus provides a favourable framework for the debt rule.
Keywords: H24; H31; H63; 330; progressive income taxes; bracket creep; political budget cycles; debt brake